Current Progress of Chinese Medicinal Treatment of Endometriosis - 江涵 沈彦 王香桂 (Chinese journal of integrative medicine, 2010)
Endometriosis（EM）is one of the common and frequently encountered gynecological diseases that seriously influences women＇s health.Its morbidity reaches 10%-15%in women at reproductive ages,and shows an evident rising tendency.In recent years,the Chinese medicine treatment of EM has won favorable therapeutic effects with few adverse reactions.A brief review on this topic has been made through analyzing and summarizing recent pertinent literatures in terms of treatment depending on syndrome differentiation,cycle treatment,external treatment,integrative medicinal treatment,so as to try to know the status quo of Chinese medicine treatment on EM,and to provide some instructive views for clinical treatment and research.